The Association Between Azathioprine Genetic Polymorphisms, Clinical Efficacy and Adverse Drug Reactions Among Egyptian Patients with Autoimmune Diseases - Abuelsoud N; Fayed H; Elkateeb E (Dove Medical Press, 2021)
Nermeen Abuelsoud,1,2 Hala Fayed,3 Engy Elkateeb4 1Department of Clinical Pharmacy Practice, Faculty of Pharmacy, The British University in Egypt, Cairo, Egypt; 2Department of Pharmacy Practice/Clinical Pharmacy, Faculty of Pharmacy, Egyptian Russian University, Cairo, Egypt; 3Department of Rheumatology and Rehabilitation, Kasr Alaini University Hospital, Faculty of Medicine, Cairo University, Cairo, Egypt; 4Department of Chemical and Clinical Pathology, Kasr Alaini University Hospital, Faculty of Medicine, Cairo University, Cairo, EgyptCorrespondence: Nermeen Abuelsoud Misr-Ismailia Road, PO Box 43, El Sherouk City, 11837, EgyptTel +00201226117118Email nersoud09@gmail.comPurpose: The study aimed to detect the frequencies of allelic variants (TPMT*3A, TPMT*3C, and TPMT*3G) in the TPMT genes in the Egyptian population and assess the association between TPMT polymorphisms and azathioprine (AZA)—clinical efficacy and adverse drug reactions among Egyptian patients with autoimmune diseases.Patients and Methods:: Design: A prospective, observational single-center clinical trial.Setting: Rheumatology and Rehabilitation Department, Kasr Alainy University Hospital, Faculty of Medicine, Cairo University.Patients: Patients attending Kasr Alainy Rheumatology Outpatient Clinic between December 1, 2017 and June 30, 2019 were included in the study after signing a consent form. TPMT genetic polymorphisms were detected for all patients, and the association between polymorphisms presence and azathioprine’s clinical efficacy and adverse drug reactions were determined.Results: A total of 150 patients with a mean age of 35.85 years were enrolled in this study. About 72% of patients were heterozygous in the TPMT*3 G460A and TPMT*3 A719G mutant alleles and 81% were wild type in the TPMT*2 G238C mutant allele. Abnormal liver function tests were detected in 42% of patients. Myelosuppression was presented as anemia which was detected in 63% of patients, leucopenia in 51%, and thrombocytopenia in 25% of patients. AZA clinical failure has occurred in 50% of patients where AZA was discontinued or shifted to another drug which occurred in 45% of patients. Myelosuppression rates were higher in homozygous patients in the three mutant alleles, but statistically significant in TPMT*2 G238C while not statistically significant in TPMT*3 G460A and TPMT*3 A719G. Females had a higher risk of immunosuppression than males (p-value 0.031).Conclusion: The study provided an overview of the genomic variations in the Egyptian population. Routine TPMT genotyping prior to the initiation of AZA therapy should be considered.Keywords: azathioprine, genetic polymorphisms, autoimmune diseases, Egyptian patients